2022
DOI: 10.3390/inorganics10050059
|View full text |Cite
|
Sign up to set email alerts
|

Sacrificial Zinc Oxide Strategy-Enhanced Mesoporosity in MIL-53-Derived Iron–Carbon Composite for Methylene Blue Adsorption

Abstract: MOF-derived carbon-based materials have attracted widespread attention due to their relatively large surface area, morphology, and their stability in water. Considering these advantages, these materials present themselves as excellent adsorbents. In this work, a novel method was designed for the fabrication of a nano zero-valent-iron (nZVI) carbon composite. The utilization of zinc oxide nanorods (ZnONRs) in the role of sacrificial consumable nuclei for the synthesis of MIL-53 sacrificial zinc oxide nanorods (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…Dekyvere et al [18] reported a novel strategy for the fabrication of nano zero-valentiron (nZVI) carbon-based mesoporous materials derived from iron-containing metalorganic frameworks (MOFs) using zinc oxide nanorods as sacrificial nuclei. Here, the breakthrough idea is the utilization of the nanostructured zinc oxide under the shape of nanorods (i.e., aspect ratio 10) as sacrificial consumable nuclei for shaping the final highly porous materials (with specific surface area in the 185-270 m 2 /g range).…”
mentioning
confidence: 99%
“…Dekyvere et al [18] reported a novel strategy for the fabrication of nano zero-valentiron (nZVI) carbon-based mesoporous materials derived from iron-containing metalorganic frameworks (MOFs) using zinc oxide nanorods as sacrificial nuclei. Here, the breakthrough idea is the utilization of the nanostructured zinc oxide under the shape of nanorods (i.e., aspect ratio 10) as sacrificial consumable nuclei for shaping the final highly porous materials (with specific surface area in the 185-270 m 2 /g range).…”
mentioning
confidence: 99%